Comprehensive Improvement of Cardiology Inpatient Transfers: A Bed-availability Triggered Approach. Issue 5 (8th September 2022) - Moore, Judson A.; Eilers, Lindsay F.; Willis, Amanda J.; Chance, Michael D.; La Salle, Julie A.; Delgado, Ellen H.; Bien, Katie M.; Goldman, Jordana R.; Sheth, Shreya S.
Abstract : Introduction: Patient transfers pose a potential risk during hospitalizations. Structured communication practices are necessary to ensure effective handoffs, but occur amidst competing priorities and constraints. We sought to design and implement a multidisciplinary process to enhance communication between pediatric cardiovascular intensive care unit and cardiology floor teams with a comprehensive approach evaluating efficiency, safety, and culture. Methods: We conducted a prospective quality improvement study to enact a bed-availability triggered bedside handoff process. The primary aim was to reduce the time between handoff and unit transfer. Secondary metrics captured the impact on safety (reported safety events, overnight transfers, bounce backs, and I-PASS utilization), efficiency (transfer latency, unnecessary patient handoffs, and cumulative time providers were engaged in handoffs), and culture (team members perceptions of satisfaction, collaboration, and handoff efficiency via survey data). Results: Eighty-two preimplementation surveys, 26 stakeholder interviews, and 95 transfers were completed during the preintervention period. During the postintervention period, 145 handoffs were audited. We observed significant reductions in transfer latency, unnecessary handoffs, and cumulative provider handoff time. Overnight transfers decreased, and no negative impact was observed in reported safety events or bouncebacks. Survey results showed a positive impact on collaboration, efficiency, and satisfaction among team members. Conclusions: Developing safer handoff practices require a collaborative, structured, and stepwise approach. Advances are attainable in high-volume centers, and comprehensive measurement of change is necessary to ensure a positive impact on the overall patient and provider environment.